THE EFFECTIVENESS OF THE SPECIAL DEVELOPMENT PROGRAM FOR CHILDREN AT THE CLASS II JUVENILE REHABILITATION CENTER IN KARANGASEM, BALI - Virgayanti, Ni Ketut Anik; Astara, Prof. Dr. Drs. I Wayan Wesna; Sukandia, Dr. I Nyoman (YURIS: Journal of Court and Justice, 2024)
The effectiveness of the Class II Juvenile Rehabilitation Center (LPKA) Program in Karangasem Regency is an important focus in safeguarding the development of juveniles involved in criminal proceedings. In an increasingly complex era, the importance of a sensitive and responsive approach to their needs is necessary. The purpose of special development program for juveniles is to prevent recidivism, protect children's human rights, and build an inclusive society. this research aims to examine and analyze the effectiveness of the Class II Juvenile Rehabilitation Center special development program in Karangasem regency as well as identify any factors that influence the effectiveness of the Class II Juvenile Rehabilitation Center special development program in Karangasem regency. This research applies descriptive empirical method by exploring field data through interviews and observations. The findings indicated that the effectiveness of the development program has had a positive impact with adequate facilities and cooperation with external parties. Despite obstacles such as emotional problems and adjustment difficulties, efforts continue to be carried out towards improving the program. However, there are still obstacles in improving skills training facilities. In conclusion, the effectiveness of the special development program for juveniles at Class II Juvenile Rehabilitation Center (LPKA) in Karangasem Regency can be concluded as significant, with efforts to continue improving its quality in preparation for the juvenile to return to the community in a productive manner.